Estudo teórico: da adsorção de etanol em clusters de Cun e Aun (n = 10-20) - Martínez, Manuel Ricardo Fuentes (Universidade Federal de São Carlos, 2021)
In this work, we study aggregates, which we will call clusters of copper and gold with and without the adsorbed ethanol molecule. First, we investigated the most favorable positions for ethanol adsorption to occur in metallic clusters. Then, we used three methods to obtain, a priori, these positions with possession only of the clusters without performing calculations with the adsorbed molecule. These methods are the Fukui indices, the interaction of point charges around the metallic cluster, and a geometric index, which gives how close or far apart the metallic atoms are in the isolated cluster in question. These positions obtained are then confronted with those from a later calculation of the cluster and ethanol set. With this, we established the predictive power of the methods used to obtain the best adsorption positions. Gold and copper nanoclusters have been extensively studied in several theoretical works using density functional theory. The present work used the density functional theory, using the hybrid exchange and correlation functional B3LYP and the base set def-SVP and later def-TZVPP. The objective is to compare energy character between several clusters with sizes of 10 to 20 atoms, obtained from the literature. Our studies do not have the nature of being systematic. Instead, develop and carry out a critical analysis of models that could study the adsorption of molecules in metallic clusters. Several theoretical studies indicate that ethanol preferentially adsorbs on metallic nanoclusters via nucleophilic attack by the oxygen-free electronic pair. This work includes the D3 Grimme scattering approximation to correct for van der Waals (vdW) effects. According to the results obtained, it was observed that there is no clear relationship between the energy analysis of the clusters, such as the binding energy (BE) (or the second energy difference (∆2E)) and the adsorption energy of ethanol (Eads). After adsorption of the ethanol molecule, some gold clusters deform their initial geometry in the region of 12 to 18 atoms. This problem is not frequent in copper clusters. The adsorption energy in copper clusters varies from -0.65 to -1.16 eV and, for gold clusters, the adsorption energy varies from -0.40 to -0.75 eV. Our studies showed that metallic clusters might have different stabilities due to geometric deformation against the adsorption of molecules. The studies carried out here will help the development of ethanol catalysis in metallic clusters.
Estudio teórico: de la adsorción de etanol en clusters de Cun y Aun (n= 10-20)
Keywords: Adsorção molecular; DFT; Cluster; CIENCIAS EXATAS E DA TERRA::QUIMICA